Pressure group competition and GMO regulations in Sub-Saharan Africa: Insights from the Becker model - Takeshima, Hiroyuki; Gruère, Guillaume P. (Walter de Gruyter GmbH, 2011)
It is widely acknowledged that pressure groups play influential roles with regard to decision making on the agricultural and food use of genetically-modified organisms (GMO) in developing countries, especially in Sub-Saharan Africa (SSA). However, there has been relatively minimal examination of when these lobbying efforts actually influence GMO policies, and how such influence changes when other exogenous constraints associated with GMO improve. Using the model of competition between pressure groups developed by Becker (1983), this paper shows that if anti-GMO lobbying appears to be working, it is likely because conditions in SSA are unfavorable to the introduction of GMO. This result is validated by a discussion of existing capacity constraints for the development, regulation, and dissemination of GMO in SSA countries, and of how these constraints may make conditions less favorable despite the reported potential benefits of GMO. The findings of this paper confirm the importance of relaxing capacity and institutional constraints, and suggest that these constraints should be addressed before considering a possible lack of political will for promising GMO in SSA countries. Political influence may not have as much of an impact on the slow adoption of GMO by SSA countries as insufficient scientific and institutional capacity.